Thermodynamics for engineers - Potter, Merle C.; Somerton, Craig W. (New York : McGraw-Hill Education, 2020)
Schaum?s Outline of Thermodynamics for Engineers, Fourth Edition is packed with four sample tests for the engineering qualifying exam, hundreds of examples, solved problems, and practice exercises to test your skills. This updated guide approaches the subject in a more concise, ordered manner than most standard texts, which are often filled with extraneous material.
Includes index.
Previous edition: New York: McGraw-Hill, 2014.
Keywords: Thermodynamics; Thermodynamics -- Problems, exercises, etc; Thermodynamics; Problems and exercises